A Sociological Explaining of Attitudes toward Violence Against Women among Male College Students in Mazandaran Province - Samaneh Eskandary; Akbar Aliverdinia; Mohammad Esmaeil Riahi; Memar Rahmatollah (مطالعات اجتماعی روان‌شناختی زنان, 2021)
This study aimed to investigate social and cultural factors affecting students’ attitudes toward violence against women. This study was conducted using a survey method among 400 male students of public universities in Mazandaran province who were selected based on stratified probabilistic sampling method and using theories of Liberal Feminism and Social Learning. The results revealed that the majority of participants (72/5%) had a negative, more than 26% of them had a medium, and more than 1% of them had a positive attitude toward violence against women. Also, the results of multiple regression analysis show that the independent variables of perceived norm qualities of significant others, traditional attitudes towards women, perceived reaction qualities of significant others, perceived rewards, and traditional marital role expectations, respectively have the greatest impact on the dependent variable. In general, the results confirm the propositions of the theories of liberal feminism and social learning and they show that the issue of violence against women and the attitudes toward it, is not inevitable, rather it is created under the influence of the structure and ideology that governs society and the social ties of the individual with those around him and the rewards and punishments he receives during his actions. Keywords Attitude, Violence against Women, Liberal Feminism, Social Learning